Telecollaboration applications in foreign language classrooms - Montaner-Villalba, Salvador 1973-; Di Sarno-Garcia, Sofia 1994-; Gimeno Sanz, Ana Maria (IGI Global, 2023)
Telecollaboration Applications in Foreign Language Classrooms reports current empirical research methods and reviews relevant theoretical advances in the implementation of telecollaboration for the teaching of foreign languages, second languages, languages for specific purposes, and telecollaboration as a means to foster intercultural and pragmatic competence. Covering key topics such as augmented reality, second language learning, and foreign language learning, this premier reference source is ideal for policymakers, administrators, scholars, researchers, academicians, instructors, and students